Two new species of Mycterothrips (Thysanoptera: Thripidae) from Southwestern China - Li, Yajin; Li, Zhengyue; Zhang, Hongrui (Zootaxa, 2017)
Mycterothrips gongshanensis sp.n. and M. yelangi sp.n. are described from Southwestern China. Both species have been collected from tea (Camellia sinensis), and M. gongshanensis sp.n. is a potential pest in tea gardens. An identification key is provided to the Mycterothrips species recorded from China.